Angioplasty in the treatment of median arcuate ligament compression syndrome combined with splenic aneurysm: A case report - Sai Xiang; Xiaodong Wang; Jifu Lai (Annals of Vascular Surgery - Brief Reports and Innovations)
Median Arcuate Ligament Syndrome (MALS) is characterized by clinical manifestations resulting from the direct compression of the celiac trunk by the median arcuate ligament. Symptoms typically include postprandial abdominal pain, nausea, vomiting, and weight loss. The patient, a 69-year-old female, presented with complaints of coughing, abdominal pain, and weight loss following positional changes. Physical examination revealed a systolic vascular murmur in the mid and upper abdomen, which was accentuated during exhalation. Abdominal aortic CTA indicated severe stenosis at the origin of the celiac trunk and localized dilation of the splenic artery. These findings strongly suggested MALS. In this case, we proceeded with endovascular treatment, achieving early symptom relief. Given the rarity of MALS and its nature as a diagnosis of exclusion, the diagnosis and treatment approach may lack clarity. Symptom relief can be achieved with a variety of interventions including celiac ganglionectomy as well as open, laparoscopic, or robotic intervention. Endovascular treatment for MALS has been questioned in the past, the diagnosis and treatment of MALS must be patient-centered, tailored to the individual needs of each patient.